2020
DOI: 10.1183/23120541.00294-2019
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity for cystic fibrosis: perceptions of people with cystic fibrosis, parents and healthcare professionals

Abstract: BackgroundThe benefits of physical activity (PA) for people with cystic fibrosis (pwCF) are widely accepted, yet how PA is promoted and utilised by pwCF is unclear.MethodAn online questionnaire to explore attitudes, practices and promotion of PA in cystic fibrosis was completed by healthcare providers (HCP), pwCF and parents/caregivers.Results351 respondents (105 HCP, 120 pwCF, and 126 parents/caregivers) from 12 countries completed the survey. Importance of PA was rated highly by the majority of respondents. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…On the other hand, the healthy subjects who participated in the study were more active, with 83% showing strenuous physical activity and 17% presenting medium-intensity activity. Supervised training is more efficient in long-term adherence to the exercise program than an unsupervised or partially supervised exercise program [ 31 , 32 ]. Furthermore, advances in technology have contributed to the engagement of patients with CF in exercise training, as López-Liria et al demonstrated that video games can be an excellent alternative to conventional treatment and recorded high levels of adherence to active components, making the treatment more entertaining [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the healthy subjects who participated in the study were more active, with 83% showing strenuous physical activity and 17% presenting medium-intensity activity. Supervised training is more efficient in long-term adherence to the exercise program than an unsupervised or partially supervised exercise program [ 31 , 32 ]. Furthermore, advances in technology have contributed to the engagement of patients with CF in exercise training, as López-Liria et al demonstrated that video games can be an excellent alternative to conventional treatment and recorded high levels of adherence to active components, making the treatment more entertaining [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly detrimental for CF girls since participation in habitual PA has been shown to slow the rate of decline in lung function, and lower levels of habitual PA may partially explain the poorer survival rate of females with CF [ 32 ]. Although there are studies aimed at finding barriers to PA reported by CF youth [ 15 ], there are no special obstacles in the case of CF girls. However, there are qualitative studies which highlight gender differences in young CF adults about perceptions of living with CF.…”
Section: Discussionmentioning
confidence: 99%
“…Additional health benefits are the improvement of cardiorespiratory fitness by increasing the endurance and strength of respiratory muscles [ 9 ], bone mineral density [ 13 ], food intake and enhancing nutritional status [ 14 ]. These advances positively influence psychological and emotional dimensions such as self-confidence and sense of control [ 15 ], which stimulate the perception of a better quality of life [ 14 ]. Several reasons have thus made PA an important part of CF therapy and rehabilitation [ 3 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The existing guidelines that are currently used in clinical practice, and informed the topic selections, were also previously identified via an international survey of healthcare professionals in CF. 19 Topics were also informed by current research priorities, as established by the CF community via a Priority Setting Partnership. 20,21 To acknowledge the holistic and simultaneous prescription of both PA and exercise within clinical guidelines, 10,11 these were not separated for the purposes of this consensus.…”
Section: Topic Selectionmentioning
confidence: 99%